The right to be forgotten: an analysis of the CJEU´s Google Spain judgment. - Carvalho, Sónia de (2015)
The CJEU recently recognized (González v. Google (case C 131/12)) a “right to be forgotten” concerning Internet search engine results. This paper analyses some issues raised by this decision regarding to the application of data protection Directive 95/46/EC to search engines.